Biocontrol potential of Cladosporium sphaerospermum against the wheat powdery mildew fungus Blumeria graminis f. sp. tritici - Zhu 朱, Mo 墨; Zhang, Wanwan; Duan, Xiao; Yan, Shaonan; Cai, Yinxia; Gong, Shuangjun; Fahad, Shah; Qiu, Zongbo (Plant disease, 2024)
Cladosporium spp. are known to be mycoparasites and inhibit phytopathogenic fungi. However, so far, little information is available on the impacts of Cladosporium spp. on powdery mildews. Based on the morphological characteristics and molecular analysis, C. sphaerospermum was identified as a mycoparasite on the wheat powdery mildew fungus (Blumeria graminis f. sp. tritici, Bgt, recently named as B. graminis s. str.). C. sphaerospermum was capable of preventing colony formation and conidial distribution of Bgt. The biomasses of Bgt notably decreased by 1.3, 2.2, 3.6 and 3.8 times at 2 dpi, 4 dpi, 6 dpi and 8 dpi, respectively. In addition, biomasses of C. sphaerospermum at 2 dpi, 4 dpi, 6 dpi and 8 dpi significantly increased to 5.6, 13.9, 18.2 and 67.3 times, respectively. In vitro, C. sphaerospermum exudates significantly impaired appressorial formation of Bgt. Thus, C. sphaerospermum acts as a potential biological control agent by suppressing the formation, distribution and development of Bgt conidia and is a viable alternative for managing the wheat powdery mildew. These results suggest that C. sphaerospermum is an antagonistic parasite of the wheat powdery mildew fungus, and hence, provide new knowledge about the biological control of phytopathogenic fungi.